2012
DOI: 10.1111/j.1600-0463.2012.02969.x
|View full text |Cite
|
Sign up to set email alerts
|

OK‐432‐stimulated chemokine secretion from human monocytes depends on MEK1/2, and involves p38 MAPK and NF‐κB phosphorylation, in vitro

Abstract: Interaction between the immune system and cancer cells allows for the use of biological response modifiers, like OK-432, in cancer therapy. We have studied the involvement of monocytes (MOs) in the immune response to OK-432 by examining MCP-1, MIP-1α and MIP-1β secretion, in vitro. OK-432-induced IL-6/TNF-α secretion has previously been shown to depend on mitogen-activated protein kinases (MAPKs) ERK1/2 and p38, and we therefore investigated the role of these MAPKs in OK-432-induced chemokine secretion. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Monocytes are members of the MNP compartment and precursors of macrophages. MNP are versatile cells , which, e.g., secrete different cytokines following activation . Monocyte function is classically studied by measuring cytokine secretion after in vitro stimulation by LPS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes are members of the MNP compartment and precursors of macrophages. MNP are versatile cells , which, e.g., secrete different cytokines following activation . Monocyte function is classically studied by measuring cytokine secretion after in vitro stimulation by LPS .…”
Section: Discussionmentioning
confidence: 99%
“…MNP are versatile cells , which, e.g., secrete different cytokines following activation . Monocyte function is classically studied by measuring cytokine secretion after in vitro stimulation by LPS . LPS stimulation triggers secretion of pro‐inflammatory interleukins (IL‐1β, IL‐6, TNF‐α) and modulates chemokine (MCP‐1) secretion .…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes are members of the MNP system [4], which secrete such cytokines in particular following activation [24, 25]. Monocyte function may be assessed by measuring cytokine secretion after in vitro stimulation of the TLR-4 receptor [26].…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte function may be assessed by measuring cytokine secretion after in vitro stimulation of the TLR-4 receptor [26]. Such stimulation promotes the secretion in particular of pro-inflammatory interleukins (IL-1β, IL-6, TNF-α) [25], and modulates chemokine (MIP-1α/β, MCP-1) secretion [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Syk is also required for cytokine production with MyD88 adaptor protein pathways [ 30 ]. Numerous studies have demonstrated that Syk-mediated mitogen-activated protein kinases play a vital role in the expression of inflammatory genes [ 31 33 ]. Syk mediates NLRP3 inflammasome activation [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%